Wild betta species (Teleostei: Osphronemidae) in Pergam Peat Swamp Forest, Bangka Island, Indonesia - ALIFA KARINA WIJAYA; NANTASA EKA ANDRAINI; KISMIYATI KISMIYATI; JOSIE SOUTH; RENI AMBARWATI; VERYL HASAN (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Wijaya AK, Andraini NE, Kismiyati, South J, Ambarwati R, Hasan V. 2026. Wild betta species (Teleostei: Osphronemidae) in Pergam Peat Swamp Forest, Bangka Island, Indonesia. Biodiversitas 27 (7): d270702. https://doi.org/10.13057/biodiv/d270702. Bangka Island is a hotspot for the diversity of wild betta species (Teleostei: Osphronemidae) in Southeast Asia. However, ecological information regarding species distribution and habitat associations in these blackwater ecosystems remains limited. This study evaluated the diversity, dominance, and habitat distribution of wild betta species in the Pergam Peat Swamp Forest, Bangka Island, Indonesia. Sampling was conducted across upstream, midstream, and downstream habitats using standardized field surveys and environmental measurements. The 166 individuals recorded, representing four species, namely Betta burdigala, B. chloropharynx, B. edithae, and B. schalleri. The highest abundance of wild betta was obtained from the B. edithae, while the lowest abundance was B. chloropharynx. The Diversity Index (H') ranged from 0.85 to 1.20, indicating low to moderate diversity, while the Evenness Index (E) ranged from 0.61 to 0.89, suggesting a relatively even distribution of individuals among species. The Dominance Index (C) ranged from 0.32 to 0.54, reflecting low to moderate dominance. The highest H' and E values were recorded at Station 1 during the dry season, while the lowest C value was also observed at this station, indicating a more stable community structure. The study highlights the peat swamp habitats' ecological importance as refuges for endemic and specialized freshwater fishes. Ongoing habitat degradation, vegetation disturbance, and hydrological alteration may threaten the persistence of these blackwater fish communities. Therefore, long-term ecological monitoring and peat-swamp conservation are urgently needed to support biodiversity preservation in Bangka Island.